Clinical profiling of subclinical hypothyroidism at presentation at tertiary care center - Mishra, Sanjay; Gupta, Arjit (International Journal of Research in Medical Sciences, 2019)
Background: Subclinical hypothyroidism (SCH) is defined as serum thyroid-stimulating hormone (TSH) level above upper limit of normal despite normal levels of serum free thyroxine, stable over a period of one month in the absence of any non thyroidal illness. Present study is aimed at evaluating prevalence of SCH in developing countries and evaluating the clinical spectrum of these patients highlighting the importance of treatment of SCH. Methods: Total number of 120 patients with established SCH was enrolled for the study over 3 years. The values were measured by third generation non-isotopic immunochemiluminiscence method using the standard protocol as indicated in the kit. Results: Patients were aged 15-50 years old. The most common manifestation was generalized weakness, lethargy and tiredness (60%) followed by generalized body ache (52.5%). 46.7% % of the patients had complaints of weight gain. Triglyceride levels and serum cholesterol levels were deranged in 28.3% of all cases. Body mass index was increased in 28.3% of all patients with obesity in only 2 patients. 15 patients (11.7%) were found to be anaemic with increased MCV and MCH/MCHC, attributable to hypothyroidism. Conclusions: These symptoms caused significant debilitated life style and poor outcome in SCH patients. Treatment of these patients can help in improving their lifestyle and perform better on daily basis.